Application of OptiTrack Motion Capture Systems in Human Movement Analysis: A systematic Literature Review - Nagymáté, Gergely; M. Kiss, Rita (Recent Innovations in Mechatronics, 2018)
With the spreading of motion analysis decisions to invest into a new system demand scientific reference applications. The aim of the present systematic review is to reveal the biomechanical scientific applications of OptiTrack motion capture systems and to overview documented usage conditions and purposes. Six major scientific literature databases were used (PubMed, PubMed Central, ScienceDirect, IEEE Xplore, PLOS and Web Of Science). An OptiTrack camera system had to be used for human or biologically related motion capture. A total of 85 articles were included, 4 out of which dealt with the validation of OptiTrack systems and 81 utilized the system for biomechanical analyses. The data analysed and extracted from the system validation studies included: description of the validated and the reference system, measured features and observed errors. The data extracted from the utilizing studies also included: OptiTrack application, camera type and frequency, marker size, camera number, data processing software and the motion studied. The review offers a broad collection of biomechanical applications of OptiTrack motion capture systems as scientific references for certain motion studies. The review also summarizes findings on the accuracy of the systems. It concludes that the method descriptions of system usage are often underspecified.